Helping Students Become Proficient Physics Problem Solvers Through Problem-Based Learning - Sarkingobir, Yusuf; Bello, Abdulaziz (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study investigated the efficacy of Problem-Based Learning (PBL) in enhancing students' problem-solving abilities in physics education, addressing the lack of effective methodologies in nurturing this crucial skill. Utilizing a quasi-experimental design, 58 secondary school students from Nigeria were divided into an experimental group, which received PBL instruction, and a control group, which received traditional teaching methods. Over three months, both groups were assessed using an essay test format before and after the intervention, focusing on problem-solving abilities related to force and motion concepts. Descriptive and inferential statistical analyses were employed to evaluate the pretest, posttest, and n-gain scores, revealing significant improvements in problem-solving abilities within the experimental group compared to the control group. Specifically, students exposed to the PBL model exhibited higher average scores and greater improvement in problem-solving skills across various indicators, including understanding the problem, developing a plan, implementing the plan, and reflecting on solutions. The findings underscored the effectiveness of the PBL model in fostering active engagement, collaborative learning, and structured problem-solving processes, aligning with contemporary educational approaches that prioritize practical skill development and critical thinking. This study contributed to the growing body of literature supporting the efficacy of PBL in enhancing problem-solving abilities, highlighting its potential to cultivate a dynamic learning environment conducive to the development of essential skills in physics education.